2000
DOI: 10.1097/00001756-200009280-00034
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent mossy fibers preferentially innervate parvalbumin-immunoreactive interneurons in the granule cell layer of the rat dentate gyrus

Abstract: Detection of vesicular zinc and immunohistochemistry against markers for different interneuron subsets were combined to study the postsynaptic target selection of zinc-containing recurrent mossy fiber collaterals in the dentate gyrus. Mossy fiber collaterals in the granule cell layer selectively innervated parvalbumin-containing cells, with numerous contacts per cell, whereas the granule cells were avoided. Under the electron microscope, those boutons made asymmetrical contacts on dendrites and somata. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…In control animals perfused, sectioned, and Timm-stained in parallel with the kainate-treated rats, the somata and proximal dendrites of granule cell layer interneurons were prominently outlined by Timm-positive fibers (Fig. 2, C2), as previously described (Ribak and Peterson, 1991;Blasco-Ibanez et al, 2000). Few Timm-positive elements were observed to extend into the inner molecular layer of saline-treated control animals ( Fig.…”
Section: Experiments 4: Combined Timm Staining and Parvalbumin Immunocsupporting
confidence: 67%
See 1 more Smart Citation
“…In control animals perfused, sectioned, and Timm-stained in parallel with the kainate-treated rats, the somata and proximal dendrites of granule cell layer interneurons were prominently outlined by Timm-positive fibers (Fig. 2, C2), as previously described (Ribak and Peterson, 1991;Blasco-Ibanez et al, 2000). Few Timm-positive elements were observed to extend into the inner molecular layer of saline-treated control animals ( Fig.…”
Section: Experiments 4: Combined Timm Staining and Parvalbumin Immunocsupporting
confidence: 67%
“…The loss of hilar mossy cells, which normally project to the inner molecular layer, presumably triggers mossy fiber sprouting into this denervated subregion, which results in the gradual re-innervation of both inhibitory interneurons and granule cells that were partially deafferented by the initial mossy cell degeneration. Unlike granule cells, dentate inhibitory interneurons normally receive granule cell input (Ribak and Peterson, 1991;Blasco-Ibanez et al, 2000;Seress et al, 2001), and can therefore be assumed to possess all of the components of the intracellular signaling pathways that mediate normal interneuron-granule cell influences. The possibility that granule cells constitutively lack the cellular apparatus to respond fully to abnormal input from other granule cells might underlie the observation that direct interactions among granule cells are relatively weak in the synaptically reorganized dentate gyrus (Scharfman et al, 2003), although this is clearly conjectural.…”
Section: Possible Functional Implicationsmentioning
confidence: 99%
“…2a). We noted that some of the neurons that contained SDF-1-mRFP1-expressing vesicles had the general morphology of basket cells, a major type of DG interneuron (Blasco-Ibáñez et al, 2000). Indeed, these particular SDF-1-mRFP1-expressing cells also expressed parvalbumin, a marker for some types of DG basket cells (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…In keeping with this, interneurones positioned in the inner molecular and granular layers show immunoreactivity for all Ca v 3 isoforms from the T-type Ca 2+ channel family (McKay et al 2006; Vinet & Sik, 2006), let alone the dense localization of T-type Ca 2+ channel gene transcripts in this area (Talley et al 1999) and the rich innervation of parvalbumin-immunoreactive interneurones by Timm-stained mossy fibre collaterals (Blasco-Ibanez et al 2000; Seress & Gallyas, 2000). Although T-type Ca 2+ channels are generally not involved in evoked neurotransmitter release, they can initiate slow release from non-axonal sites (Cueni et al 2009) and recent evidence in dorsal horn neurones (Jacus et al 2012) and layer III enthorinal cortex (Huang et al 2011) has shown that they can potently inhibit glutamate release.…”
Section: Discussionmentioning
confidence: 90%